Determinants of trust in the European Central Bank - Justina A. V. Fischer; Volker Hahn (Stockholm School of Economics, The Economic Research Institute (EFI), 2008)
In this paper we study the determinants of citizens' trust in the European Central Bank during the start-up phase from 1999-2004. Using a country panel based on the Eurobarometer survey, we find that higher inflation rates reduce trust. Thus people appear to evaluate the performance of the ECB on the basis of its success in achieving its primary objective, namely price stability. However, national income also has a strong impact, which poses a dilemma to the ECB, as there is a general consensus among academics that monetary policy cannot increase economic growth in the long run. Unemployment does not have a significant impact on trust in the ECB, while unemployment spending exerts a trust-building impact. Possibly, automatic stabilizers serve as substitutes for ECB interventions, which would lower people's trust. Interestingly, active labor market policies, which can be interpreted as proxies for the public's perception of the urgency of the problem of high unemployment, tend to decrease trust.
Keywords: C33; E58; H50; Z13; 330; ECB; trust; European Union; Eurobarometer; panel data; behavioral economics; Zentralbank; Geldpolitik; Inflationsrate; Vertrauen; Verhaltensökonomik; Panel; EU-Staaten